Serotonin 5-HT2A Receptor Activation Blocks TNF-α Mediated Inflammation In Vivo - Nau, Felix, Jr; Yu, Bangning; Martin, David; Nichols, Charles D. (PLOS ONE, 2013)
Tumor necrosis factor alpha (TNF-α) plays a key role in inflammation, and its production and signaling contribute to many inflammatory related diseases. Recently, we discovered that selective activation of serotonin 5-HT2A receptors with the agonist (R)-DOI produces a super-potent blockade of proinflammatory markers in primary rat aortic smooth muscle cells. Here, we demonstrate that systemic administration of (R)-DOI can block the systemic effects of TNF-α in whole animal, with potent anti-inflammatory effects in the aortic arch and small intestine. This includes blockade of TNF-α-induced expression of pro-inflammatory cell adhesion (Icam-1, Vcam-1), cytokine (Il-6, IL-1b), and chemokine (Mcp-1, Cx3cl1) genes, and expression of VCAM-1 protein in the intestine. Further, systemic (R)-DOI also prevents the TNF-α-induced increase of circulating IL-6. Importantly, utilizing receptor selective antagonists, we have demonstrated that the mechanism underlying the systemic anti-inflammatory effects of (R)-DOI is activation of serotonin 5-HT2A receptors. Our results highlight a powerful new role for the serotonin 5-HT2A receptor in inflammatory processes, and indicate that agonism of serotonin receptors may represent an effective and novel approach to develop powerful small molecule therapeutics for inflammatory diseases and conditions such as atherosclerosis and inflammatory bowel disease.